2023
DOI: 10.1080/22221751.2023.2239940
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of macrophages and CD8 T cells in bronchoalveolar lavage fluid is associated with latent tuberculosis infection

Abstract: Mycobacterium tuberculosis (Mtb) infection, including active tuberculosis (TB) and latent Mtb infection (LTBI), leads to diverse outcomes owing to different host immune responses. However, the immune mechanisms that govern the progression from LTBI to TB remain poorly defined in humans. Here, we profiled the lung immune cell populations within the bronchoalveolar lavage fluid (BALF) from patients with LTBI or TB using single-cell RNA sequencing (scRNA-seq). We found that Mtb infection substantially changed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The single-cell clustering analysis conducted in non-human primate TB models revealed an elevated accumulation of LAG-3 on T cells and macrophages as TB infection and BCG injection duration extended, aligning with the outcomes from our subcomponent immune infiltration analysis ( Figures 3A-C , 5 , 6 ). A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection ( Yang et al., 2023 ). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection ( Yang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The single-cell clustering analysis conducted in non-human primate TB models revealed an elevated accumulation of LAG-3 on T cells and macrophages as TB infection and BCG injection duration extended, aligning with the outcomes from our subcomponent immune infiltration analysis ( Figures 3A-C , 5 , 6 ). A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection ( Yang et al., 2023 ). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection ( Yang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection (Yang et al, 2023). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection (Yang et al, 2023). Boer MC et al observed that BCG vaccination induced KLRG1 expression on BCG-stimulated CD8+ T cells, leading to a significant reduction in proliferation (Boer et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The single-cell clustering analysis conducted in non-human primate TB models revealed an elevated accumulation of LAG-3 on T cells and macrophages as TB infection and BCG injection duration extended, aligning with the outcomes from our subcomponent immune infiltration analysis 5,6). A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection (Yang et al, 2023). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection (Yang et al, 2023). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection (Yang et al, 2023). Boer MC et al observed that BCG vaccination induced KLRG1 expression on BCG-stimulated CD8+ T cells, leading to a significant reduction in proliferation (Boer et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…The single-cell clustering analysis conducted in non-human primate TB models revealed an elevated accumulation of LAG-3 on T cells and macrophages as TB infection and BCG injection duration extended, aligning with the outcomes from our subcomponent immune infiltration analysis 5,6). A separate study indicated a relationship between the interaction of macrophages and CD8 T cells in bronchoalveolar lavage and latent TB infection (Yang et al, 2023). The Monocyte macrophage (MM)-CCL23 pathway primarily attracted CD8-CCR6 T cells through the CCL20/CCR6 axis, a key feature associated with protective immunity in latent TB infection (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%